THE EFFECTS OF CEMENT PARTICULATE DISCHARGE ON TWO TREES AND A COMMON SHRUB IN ASHAKA, GOMBE STATE - Nsor, Charles Ayuk; Joseph, Faith; Usim, Nya John; Elaigwu, Atukpa Mishael; Oride, Mary Godday; Patrick, Datheh; Abubakar, Binta (FUDMA JOURNAL OF SCIENCES, 2025)
Air pollution causes morphological alterations in plants which may affect the plant either through direct toxic effects or indirectly by altering the physiology of the plant. The trees (Azadirachta indica, Balanites aegyptiaca) and shrub (Calotropis procera) were sampled from a distance gradient of (0km, 2km, 4km and 6km) using systematic random selection. Leaf samples from both polluted and control sites were collected and treated using leaf maceration method. Results revealed variations in stomatal size and frequencies of samples from polluted and the control sites. Soil samples were chemically analyzed. Stomata size and frequency decreased with increasing distance from source of pollution. Areas closer to the factory were more affected than those further away (0 km > 2 km >4 km >6 km) from the factory site. Chlorophyll content, leaf abundance, species density and basal area increased significantly with distance from the factory site. Similarly, Co and CaO content in dust around the factory site were very high 75 – 90 % and 41.7 % respectively. The results provide evidence that cement particulate discharge is hazardous to leaf health. This study highlights the need to periodically conduct EIAs so that informed actions can be taken to safeguard the health and safety of humans and biodiversity. We recommend further research and EIA beyond 0 - 6 km radius to inform intervention actions. Our findings suggest environmental threats with dire consequences for Agriculture and human health, as the pollutants could bio-magnify and infiltrate the food chain over time.